2016
DOI: 10.1007/s11517-016-1559-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative acceleration measurements to quantify improvement in tremor during deep brain stimulation surgery

Abstract: Intraoperative acceleration measurements to quantify improvement in tremor during deep brain stimulation surgery. Medical and Biological Engineering and Computing, Springer Verlag, 2017, 55 (5) AbstractDeep brain stimulation (DBS) surgery is extensively used in the treatment of movement disorders. Nevertheless, methods to evaluate the clinical response during intraoperative stimulation tests to identify the optimal position for the implantation of the chronic DBS lead remain subjective. In this paper, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…But those systems were not designed to be used in different clinical centers or during stimulation tests performed through an exploration electrode. In a previous study, we have demonstrated the use of our system in 15 DBS surgeries in two different clinical centers, the possibility to visualize and revisit recorded data during surgery and the possible influences of quantitative evaluations on the choice of the final implant position of the lead for chronic stimulation (Shah et al, 2016b). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But those systems were not designed to be used in different clinical centers or during stimulation tests performed through an exploration electrode. In a previous study, we have demonstrated the use of our system in 15 DBS surgeries in two different clinical centers, the possibility to visualize and revisit recorded data during surgery and the possible influences of quantitative evaluations on the choice of the final implant position of the lead for chronic stimulation (Shah et al, 2016b). …”
Section: Discussionmentioning
confidence: 99%
“…In order to quantify the clinical improvement for each stimulation amplitude, a previously developed analysis method in Matlab (R2014b) was used (Shah et al, 2016b). As a first step, movements other than tremor were removed offline by using the smoothness priors method (Tarvainen et al, 2002) and thereafter a second order Butterworth low pass-filter was applied at 10 Hz in order to suppress noise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously published a method [42] using accelerometers to quantitatively evaluate improvement in tremor during intraoperative stimulation tests. By classifying the data collected from DBS for ET patients based on the position of the electrode with respect to the nuclei, it was possible to show that the ventro-oral (VO) nucleus of the thalamus can be as efficient in reducing tremor as the VIM [41].…”
Section: Introductionmentioning
confidence: 99%
“…The sensor was always attached at the same position on the wrist of the patient, and at each position a baseline recording was acquired before initiation of each stimulation sequence. In order to quantify the clinical improvement for each stimulation amplitude, a previously developed analysis method in Matlab (R2014b) was used (Shah et al, 2016b). As a first step, movements other than tremor were removed offline by using the smoothness priors method (Tarvainen et al, 2002) and thereafter a second order Butterworth low pass-filter was applied at 10 Hz in order to suppress noise.…”
Section: Acceleration Measurementsmentioning
confidence: 99%